International Bank Lending Channel of Monetary Policy - Albrizio, Silvia (IMF Working Papers; Working Paper ;, 2019)
How does domestic monetary policy in systemic countries spillover to the rest of the world? This paper examines the transmission channel of domestic monetary policy in the cross-border context. We use exogenous shocks to monetary policy in systemically important economies, including the U.S., and local projections to estimate the dynamic effect of monetary policy shocks on bilateral cross-border bank lending. We find robust evidence that an increase in funding costs following an exogenous monetary tightening leads to a statistically and economically significant decline in cross-border bank lending. The effect is weakened during periods of high uncertainty. In contrast, the effect is found to not vary according to the degree of borrower country riskiness, further weakening support for the international portfolio rebalancing channel.